RELOKASI KAMPUNG NELAYAN CILINCING - Dominikus Gusti Wihardani; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2023)
The Cilincing Fishermen Village, located in North Jakarta, Indonesia, has a history dating back to the 1920s as a fishing village. The majority of its residents work as fishermen, relying on the sea's resources as their livelihood. The village follows a linear two-sided settlement pattern, stretching along the road. Currently, the fishermen of Cilincing face environmental and economic challenges, such as frequent flooding and pollution from industries, impacting their livelihoods. This study also involves an analysis of social and cultural dynamics, categorizing main livelihoods, supporting livelihoods, family roles, social values, and fishing community skills before and after the relocation of the village to the sea. This will help understand the values, norms, and social practices crucial to the fishing community. The study aims to design a floating settlement that meets the physical, social, and economic needs of the fishermen, taking into account the geographical and environmental conditions. The goal is to create a sustainable relocation of the fishing community, considering architectural, economic, social, and environmental aspects that suit the fishermen's and marine environment's conditions. Keywords: fishing village; floating; community; fishermen; marine environment Abstrak Kampung Nelayan Cilincing, yang terletak di Jakarta Utara, Indonesia, memiliki sejarah sebagai kampung nelayan sejak tahun 1920-an, sebagian besar penduduknya bekerja sebagai nelayan yang mengandalkan hasil laut sebagai penopang kehidupan mereka, dengan pola pemukiman sejajar (linier dua sisi) merupakan permukiman yang memanjang di sepanjang jalan. Saat ini nelayan Cilincing menghadapi tantangan lingkungan dan ekonomi, seperti banjir yang sering terjadi, dan pencemaran dari industri, yang mempengaruhi penghidupan nelayan. Studi ini juga harus melibatkan analisis tentang dinamika sosial dan budaya dengan kategori yang dibagi dalam mata pencaharian utama, mata pencaharian pendukung, peran keluarga, nilai sosial, dan keterampilan komunitas nelayan sebelum dan setelah pemindahan kampung ke laut. Hal ini akan membantu memahami nilai-nilai, norma, dan praktik sosial yang penting bagi komunitas nelayan. Studi ini bertujuan untuk merancang pemukiman terapung yang memenuhi kebutuhan fisik, sosial, dan ekonomi nelayan dengan mempertimbangkan kondisi geografis dan lingkungan sekitarnya. Agar dapat Merancang relokasi permukiman nelayan yang berkelanjutan, dengan memperhatikan aspek-aspek arsitektural, ekonomi, sosial, dan lingkungan yang sesuai dengan kondisi masyarakat nelayan dan lingkungan laut.